Safety and Selection Criteria of Single-joint Hybrid Assistive Limb for Upper Limb Paralysis After Stroke: A Phase I Trial - Hiroshi OHMAE; Taku MATSUDA; Maki FUJIMOTO; Yuka NAKANOWATARI; Megumi YAMADA; Nori SATO; Kimiko UMEMURA; Ryoma MORIGAKI; Tetsuya MATSUURA; Yasushi TAKAGI (Neurologia Medico-Chirurgica)
Robotic rehabilitation is a high-intensity intervention for upper limb paralysis after a stroke. This study explored the safety and feasibility of using a single-joint hybrid assistive limb (HAL-SJ) exoskeletal device for upper limb paralysis in patients with acute stroke. In total, 11 patients with stroke (6 with moderate paralysis and 5 with severe paralysis) were enrolled between October 2021 and October 2023 in a stroke care unit. The patients underwent HAL training 3 times a week for 6 sessions. No serious adverse events related to HAL-SJ occurred, and participants demonstrated significant improvements in the Fugl-Meyer Assessment Upper Extremity (FMA-UE) and Action Research Arm Test (ARAT) (pre- vs. post-intervention; p < 0.05). The minimal clinically important difference (MCID) for FMA-UE was surpassed in 5 patients (83.3%) with moderate paralysis and 2 (40.0%) with severe paralysis. Regarding ARAT, 4 patients (66.7%) with moderate paralysis exceeded the MCID, whereas none (0.0%) with severe paralysis did. These findings suggest that HAL-SJ is both safe and feasible, particularly for individuals with moderate paralysis.